Maneras de llegar - Negroni, Juan Alberto; Universidad del Sagrado Corazón (San Juan, P.R.: Universidad del Sagrado Corazón, 2022., 2022)
Maneras de llegar por Juan Alberto Negroni es una buena muestra de esa búsqueda. Negroni nos trae esa mirada desde el otro lado, en ocasiones desde algunos de los objetos y símbolos más cotidianos de lo puertorriqueño. Su obra también muestra, desde lo visual, las múltiples capas de complejidad de nuestra historia y presente. Su trabajo también cuestiona algunas barreras del mundo del arte y crea nuevos espacios de accesibilidad desde los materiales y el color. Y sobre todo, el perfil de Juan Alberto cumple ese otro rol de la Galería de mantenerse visibilizando lo que debe ser el perfil del egresado, un profesional especialista, gestor, comprometido e innovador. Estamos confiados que esta exhibición será otra herramienta para seguir avanzando nuestro proyecto académico.
Lista de las obras presentadas: 1. Fear not my love, the absurd statements, the paradoxes are meant to fade into the background noise of the roller coasters, 2022 Mixed media on masonite 10” x 8” 2. Not very good but it looks like some people have been trying to get some more, 2021 Mixed media on cardboard 3. Interrupted development of a literary culture, 2021 Mixed media on paper 12”x 9” 4. Failed attempts to rescue a folklore the never existed because it was snatched before it existed, 2021 Tempera on wood 33.5”x 17” 5. An implicit second idea on strict establishments and typically profiled individuals that do not embody the stereotype, 2021 Mixed media on paper 12”x 9” 6. Folkloric blasphemous maneuvers, 2021 Mixed media on paper 26”x 20” 7. La Guerra fría en contra del café caliente, 2021 Mixed media on paper 16”x 10” 8. Keyhole landscape of a lost countryside from a surrealist childhood, 2021 Mixed media on paper 26”x 20” 9. Ascending/descending heartbroken allegories apologizing for miss understanding your intentions of being honest, 2021 Mixed media on paper 10. The vernacular practice of the nonbelievers, 2021 Mixed media on paper 16”x 10” 11. The conservation of tales, legends and songs that have never been written, 2021 Mixed media on paper 25.5”x 19.5”. 12. The scripts were good but they were just sent out in a bad moment, 2021 Mixed media on paper 25.5” x 19.5“ 13. Filling the gap of ideologies about miscegenation with shapes and colors, 2021 Mixed media on paper 25.5” x 19.5” 14. Homenaje al homenaje que me hiciste, 2021 Mixed media on paper 26” x 20” 15. These are the consequences of the world that conceits the same faith as you, 2021 Mixed media on canvas 10” x 8” 16. Final notice that we are still interested but we will have to go back home, 2021 Mixed media on canvas 10” x 8”
Keywords: Art--Exhibitions.; Arte--Exhibición.; Art--Puerto Rico.; Arte--Puerto Rico.; Art--Catalogs.; Negroni, Juan Alberto, 1968---Exhibitions.; Mixed media (Art)--Exhibitions.